3, 3′-Diindolylmethane attenuates inflammation and fibrosis in radiation-induced lung injury by regulating NF-κB/TGF-β/Smad signaling pathways. (16th March 2022) - Zhou, Xia; Bao, Wu-An; Zhu, Xiang; Lin, Juan; Fan, Ju-Fen; Yang, Yang; Du, Xiang-Hui; Wang, Yue-Zhen
Abstract: Objective: This study aims to investigate the protective effect of 3, 3′-diindolylmethane (DIM) on the radiation-induced lung injury (RILI) model and to explore its possible mechanism. Methods: A mouse model of RILI was established by thoracic irradiation, and dexamethasone was used as a positive drug to investigate the effect of DIM on RILI mice. Lung histopathology was analyzed by HE staining and Masson staining. Then the levels of inflammatory cytokines (TGF-β, TNF-α, IL-1β, and IL-6), inflammatory cell counts, and activity of MPO were detected. The expression of TGFβ1/Smad signaling pathway-related proteins was determined by immunohistochemistry. qPCR was used to analyze the mRNA expression levels of inflammatory factors, α‑SMA and COL1A1. The expression of COX-2, NF-κB, IκBα, PI3K, and Akt proteins was assessed by Western blot. Results: Histopathological staining of lung tissues showed that DIM administration alleviated the pulmonary inflammation and fibrosis caused by RILI. Moreover, the content of inflammatory factors such as IL-1β and IL-6, the expression of NF-κB pathway-related proteins, and the counts of inflammatory cells were inhibited in lung tissue, indicating that DIM can inhibit the NF-κB pathway to reduce inflammation. In addition, DIM could down-regulate the mRNA levels of α-SMA, COL1A1, and downregulate TGFβ1, Smad3, and p-Smad2/3 in lung tissues. Conclusion: Our study confirms that DIM has the potential to treat RILI in vivo by inhibiting fibrotic and inflammatory responses in lung tissue through the TGFβ/Smad and NF-κB dual pathways, respectively. Graphic Abstract: